Indications of 24-h esophageal pH monitoring, capsule pH monitoring, combined pH monitoring with multichannel impedance, esophageal manometry, radiology and scintigraphy in gastroesophageal reflux disease? - Vardar, Rukiye; Keskin, Muharrem (Turkish Journal of Gastroenterology, 2017)
Abstract Ambulatory esophageal pH monitoring is an essential method in patients exhibiting signs of non-erosive reflux disease (NERD) to make an objective diagnosis. Intra-esophageal pH monitoring is important in patients who are non-responsive to medications and in those with extraesophageal symptoms, particularly in NERD, before surgical interventions. With the help of the wireless capsule pH monitoring, measurements can be made under more physiological conditions as well as longer recordings can be performed because the investigation can be better tolerated by patients. Ambulatory esophageal pH monitoring can be detected within normal limits in 17%-31.4% of the patients with endoscopic esophagitis; therefore, normal pH monitoring cannot exclude the diagnosis of gastroesophageal reflux disease (GERD). Multi-channel intraluminal impedance pH (MII-pH) technology have been developed and currently the most sensitive tool to evaluate patients with both typical and atypical reflux symptoms. The sensitivity of a pH catheter test is 58% for the detection of acid reflux compared with MII-pH monitoring; further, its sensitivity is 28% for the detection of weak acid reflux compared with MII-pH monitoring. By adding impedance to pH catheter in patients with reflux symptoms, particularly in those receiving PPIs, it has been demonstrated that higher rates of diagnoses and symptom analyses can be obtained than those using only pH catheter. Esophageal manometry is used in the evaluation of patients with functional dysphagia and unexplained noncardiac chest pain and prior to antireflux surgery. The use of esophageal manometry is suitable for the detection of esophageal motor patterns and extreme motor abnormalities (e.g., achalasia and extreme hypomotility). Esophageal manometry and ambulatory pH monitoring are often used in assessments prior to laparoscopic antireflux surgery and in patients with reflux symptoms refractory to medical treatment. Although the esophageal motility is predominantly normal in patients with non-acid reflux, ineffective esophageal motility is often monitored in patients with acid reflux. In the literature, there are contradictory and an insufficient number of studies regarding radiological methods for the diagnosis of GERD. There are inconsistent values for sensitivity and specificity among the barium studies. There are inadequate studies in the literature involving scintigraphic examinations in the diagnosis of GERD, and a majority of existing studies have been conducted in the pediatric group. The results of a few studies do not provide sufficient contribution toward the implementation in clinical practice. Cite this article as: Vardar R, Keskin M. Indications of 24-h esophageal pH monitoring, capsule pH monitoring, combined pH monitoring with multichannel impedance, esophageal manometry, radiology and scintigraphy in gastroesophageal reflux disease? Turk J Gastroenterol 2017;28(Suppl 1); S16-S21 Full Text Turkish